Adoption of building information modelling in Libyan construction firms: A technological, organizational, and environmental (TOE) perspectives - Elghdban, Mohamed Ghayth; Azmy, Nurhidayah; Zulkiple, Adnan; Al-Sharafi, Mohammed A. (IOP Science, 2023)
Building information modelling (BIM), a recent information technology (IT) innovation in virtual design and construction, has been regarded as the most critical technology in the construction industry over the last decade. As a result, BIM adoption is rapidly increasing; however, this new phenomenon is not spreading as rapidly as it is in emerging regions such as Libya. The purpose of this study is to investigate the factors that affect BIM adoption at the organizational level by integrating the diffusion of innovation (DOI) theory, the technology-organization-environment (TOE) framework, and the institution theory. The data was gathered through a survey of 411 Libyan construction firms. Partial least squares were used for data analyses and to test the hypotheses. The results demonstrated that the (Perceived Relative Advantage and Compatibility) related positively to BIM adoption, while complexity related negatively to BIM adoption will top management support positively with Coercive Pressure on the adoption of BIM. The study's findings provide significant insight into crucial factors that might increase the level of BIM adoption.